PREPARATION OF THE ELECTROSPUN POLYVINYLIDENE FLUORIDE / POLYVINYL ALCOHOL SCAFFOLD AS A POTENTIAL TISSUE REPLACEMENT - Hamzah, Mohd Syahir Anwar; Razak, Nurul Amira Ab; Ng, Celine; Azize, Akmal Hafiszi Abdul; Sukor, Jumadi Abdul; Fhong, Soon Chin; Idris, Mohd Safiee; Nayan, Nadirul Hasraf Mat (IIUM Engineering Journal, 2020)
: Polyvinylidene fluoride (PVDF), a piezoelectric material, is commonly used in tissue engineering due to its potential for mimicking the electrical microenvironment of biological conditions for tissue development. In this present research, polyvinyl alcohol (PVA) was introduced into electrospun PVDF fabrication through an electrospinning process, aiming to enhance the nanofibrous membrane’s biocompatibility properties by improving the hydrophilicity properties to act as an artificial tissue scaffold. The electrospun PVDF/PVA membranes are found to be optimum at a PVDF-to-PVA ratio of 90:10 due to its excellent mechanical, morphological, and hydrophilicity conductivity properties. Fourier transform infrared (FTIR) spectroscopy verified strong hydrogen bonding interaction formed between the fluorine group of PVDF with oxygen-containing in the hydroxyl group of PVA. In-vitro cell culture showed that the enhanced hydrophilic property of electrospun PVDF/PVA could significantly enhance the cell growth. These positive results indicated that the scaffold could be implemented as artificial tissue material for tissue engineering applications. ABSTRAK: Polivinilidena fluorida (PVDF) adalah bahan piezoelektrik yang biasa digunakan dalam kejuruteraan tisu kerana potensinya menyerupai keadaan persekitaran mikro-elektrik biologi bagi perkembangan tisu. Dalam penyelidikan ini, polivinil alkohol (PVA) diperkenalkan ke dalam fabrikasi pintalan-elektro PVDF melalui proses pemintalan-elektro, yang bertujuan bagi mengembangkan sifat biokompatibiliti membran nanogentian dengan meningkatkan sifat hidrofilik bagi menjadi perancah tisu tiruan. Membran pintalan-elektro PVDF / PVA didapati optimum pada nisbah PVDF-ke-PVA, 90:10 kerana sifat kekonduksian, mekanikal, morfologi dan hidrofiliknya yang sangat baik. Spektroskopi transformasi inframerah Fourier (FTIR) mengesahkan interaksi ikatan hidrogen yang kuat terbentuk antara kumpulan fluoro PVDF dengan oksigen yang terkandung dalam kumpulan hidroksil PVA. Kultur sel secara in-vitro menunjukkan bahawa sifat hidrofilik pintalan-elektro PVDF / PVA dapat meningkatkan pertumbuhan sel secara signifikan. Hasil positif ini menunjukkan bahawa perancah ini dapat digunakan sebagai bahan tisu buatan bagi aplikasi kejuruteraan tisu.